Factors Influencing Financial Performance on Banking Companies in Indonesia: Does Financial Technology Matter? - Zahra, Hakimatuz; Innayah, Maulida Nurul; Tubastuvi, Naelati; Aryoko, Yudhistira Pradhipta (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aimed to examine the effect of company size, liquidity, and dividend policy on financial performance, using financial technology as a moderating variable and leverage as a control variable. The population of this study is conventional banking sector companies registered with the Indonesian Financial Services Authority (OJK) from 2019 to 2022. The sample collection method uses a purposive sampling technique. The number of samples obtained was 91 companies, with 137 observations. This study utilized the Fixed Effect Regression Model based on the preliminary test result for panel data regression. The results showed that liquidity and financial technology significantly positively affect financial performance. Company size and dividend policy have a negative effect on financial performance. The application of financial technology by conventional Indonesian banks can strengthen the influence of the positive relationship between firm size, liquidity, and dividend policy on financial performance. Based on this research, it is necessary to maintain an optimal level of liquidity and adopt financial technology to improve the company's financial performance. The easier and safer the financial technology the company uses will further affect the level of company performance.